ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA PT. FORTUNA INTI ALAM - Saputra, Marddyanto Dwi; Sondakh, Jullie J.; Runtu, Treesje (Universitas Sam Ratulangi, 2017)
The financial statements in principle are the result of the accounting process used to communicate the financial situation to internal and external parties that are aimed at decision making. The importance of the financial statements, then the financial statement should be prepared carefully and without errors. Financial Accounting Standards generally are not in accordance with entities whose accountability is not as significant. Therefore, the Institute of Indonesia Chartered Accountants (IAI) has issued Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) intended for entities that do not have significant public accountability and publish financial statements for general purposes for external users. This study aims to analyze the implementation of ETAP in the presentation of PT. Fortuna Inti Alam’s financial statement. The method used in this study is comparative descriptive analysis. Results of this research is based on the financial statements of 2016 show that PT. Fortuna Inti Alam has implemented ETAP but it is not fully complete yet. The Company has not presented Statement of Owner’s Equity, Cash Flow Statement, and Notes to Financial Statements. This research suggests that companies can prepare components of other financial statements in accordance with applicable standards.Keywords : Financial Statements, SAK ETAP.